You're Fired! The Causal Negative Effect of Unemployment on Life Satisfaction - Sonja C. Kassenböhmer; John P. Haisken-DeNew (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2008)
This paper examines the impact of unemployment on life satisfaction for Germany 1984-2006, using a sample of men and women from the German Socio-Economic Panel (SOEP). Across the board we find large significant negative effects for unemployment on life satisfaction. This paper expands on previous cornerstone research from Winkelmann and Winkelmann (1998) and explicitly identifies truly exogenous unemployment entries starting from 1991. We find that for women in East and West Germany, company closures in the year of entry into unemployment produce strongly negative effects on life satisfaction over and above an overall effect of unemployment, providing prima facie evidence of a reduced outside work option, large investments in firm-specific human capital or a family constraint. The compensating variation in terms of income is dramatic, indicating enormous non-pecuniary negative effects of exogenous unemployment due to company closures.
Keywords: Z1; J64; J65; J16; 330; Unemployment; life satisfaction; company closing; gender; Arbeitslosigkeit; Lebenszufriedenheit; Liquidation; Geschlecht; Deutschland